Luteal Function, Biometrics, and Echotextural Attributes in Santa Inês Ewes Superovulated with Different Total Doses of Porcine Follicle-Stimulating Hormone - Bevilaqua, Júlia Ribeiro [UNESP]; Rodriguez, Mariana Garcia Kako [UNESP]; Maciel, Giovanna Serpa [UNESP]; Vergani, Gabriel Brun [UNESP]; Fonseca, Jeferson Ferreira da; Bartlewski, Pawel Mieczyslaw; Oliveira, Maria Emilia Franco [UNESP] (MDPI, 2023)
Premature regression of corpora lutea (PRCL) may adversely affect the outcome of hormonal ovarian superstimulation in small ruminants, and the total dose of exogenous gonadotropins used may be one of the causes of this condition. There were two major objectives of the present study: (1) to evaluate the effects of different superovulatory doses of porcine follicle-stimulating hormone (pFSH) on the biometry, blood perfusion (Doppler), and echotextural characteristics of luteal structures; and, (2) to determine the usefulness of biometric, vascular, and echotextural luteal variables, as well as measurements of circulating progesterone (P4) concentrations for early detection of PRCL in superovulated Santa Inês ewes. Twenty-seven Santa Inês ewes received an intravaginal P4-releasing device (CIDR) from Days 0 to 8 (Day 0 = random day of the anovulatory period). An IM injection of d-cloprostenol (37.5 μg) was given at the time of the CIDR insertion and withdrawal. On Day 6, all the ewes received 300 IU of eCG IM and were divided into three treatment groups (each n = 9): G100 (100 mg); G133 (133 mg); and G200 (200 mg of pFSH) administered IM every 12 h in eight injections. Transrectal ovarian ultrasonography and jugular blood sampling for serum P4 measurements were performed on Days 11 to 15. On the day of embryo recovery (Day 15), all the ewes underwent diagnostic videolaparoscopy and were classified, based on their luteal characteristics, into three response groups: nCL (ewes with normal CL only); rCL (ewes with regressing CL only); and ewes with both nCL and rCL following the superovulatory regimen. Our present results indicate that the total pFSH doses of 100 mg and 200 mg result in similar ovulatory responses and luteal function/biometrics, although the percentage of donor ewes with nCL was greater (p < 0.05) for G100 compared with the G200 animals. An application of 133 mg of pFSH was associated with diminished luteogenesis. Lastly, circulating P4 concentrations, ultrasonographic estimates of total luteal area, and CL pixel heterogeneity (standard deviation of numerical pixel values) are promising markers of luteal inadequacy in superovulated ewes.
Keywords: corpus luteum; ovarian ultrasonography; progesterone; sheep; superovulation